Homebirthing in the United Kingdom during COVID-19. (September 2020) - Romanis, Elizabeth Chloe; Nelson, Anna
COVID-19 has significantly impacted all aspects of maternity services in the United Kingdom, exacerbating the fact that choice is insufficiently centred within the maternity regime. In this article, we focus on the restrictions placed on homebirthing services by some National Health Service Trusts in response to the virus. In March 2020, around a third of Trusts implemented blanket policies suspending their entire homebirth service. We argue that the failure to protect choice about place of birth during the pandemic may not only be harmful to birthing people's physical and mental health, but also that it is legally problematic as it may, in some instances, breach human rights obligations. We also voice concerns about the possibility that in the absence of available homebirthing services people might choose to freebirth. While freebirthing (birthing absent any medical or midwifery support) is not innately problematic, it is concerning that people may feel forced to opt for this.